DAMPAK PATOLOGI KELUARGA TERHADAP HUBUNGAN SOSIAL REMAJA SANTRI DI PP. SALAFIYAH ASSYAFI’IYAH AL AQSHO BANYUWANGI - Erny Indaha Zulfa; Suryadi Suryadi (Sociocouns: Journal of Islamic Guidance and Counseling, 2021)
Family is an important element in providing social support to adolescents. Entering adolescence is a transition period for children to become adults, all changes experienced by teenagers will have an impact on them. This makes teenagers as a figure who is quite sentimental about things that are personal, such as problems in the family for example. However, what if the family that should be the figure that accompanies the social development of adolescents is the party that does not have a negative impact? This article is a case study qualitative research. Data were collected using observation, interviews and documentation methods, then the data were analyzed in depth using the form of domain analysis. The research was conducted in PP. Salafiyah Assyafi'iyah Al Aqsho with the number of informants as many as 4 children who were taken based on the Problem Expression Tool (AUM) from the total number of students, namely 25 children. Based on the data obtained, adolescent students who experience problems in the family mostly experience obstacles in their social relationships. So it can be concluded that unfavorable family conditions (pathology) will have an impact on the social relationships of their adolescent children.